2017
DOI: 10.1038/s41598-017-16391-5
|View full text |Cite
|
Sign up to set email alerts
|

Social adversity and epigenetic aging: a multi-cohort study on socioeconomic differences in peripheral blood DNA methylation

Abstract: Low socioeconomic status (SES) is associated with earlier onset of age-related chronic conditions and reduced life-expectancy, but the underlying biomolecular mechanisms remain unclear. Evidence of DNA-methylation differences by SES suggests a possible association of SES with epigenetic age acceleration (AA). We investigated the association of SES with AA in more than 5,000 individuals belonging to three independent prospective cohorts from Italy, Australia, and Ireland. Low SES was associated with greater AA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
120
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(143 citation statements)
references
References 45 publications
14
120
2
Order By: Relevance
“…The difference between (predicted) DNAm and chronological age (Δage) is associated with a wide-range of health and disease outcomes. For example, DNAm age acceleration in blood is associated with all-cause mortality [15][16][17][18] , socioeconomic adversity and smoking 19 , metabolic outcomes, such as body mass index and obesity 20,21 , and brain-related phenotypes, such as Parkinson's disease, posttraumatic stress disorder, insomnia, major depressive disorder, and bipolar disorder [22][23][24]25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…The difference between (predicted) DNAm and chronological age (Δage) is associated with a wide-range of health and disease outcomes. For example, DNAm age acceleration in blood is associated with all-cause mortality [15][16][17][18] , socioeconomic adversity and smoking 19 , metabolic outcomes, such as body mass index and obesity 20,21 , and brain-related phenotypes, such as Parkinson's disease, posttraumatic stress disorder, insomnia, major depressive disorder, and bipolar disorder [22][23][24]25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…written for the R statistical computing environment, including background and color bias 571 correction, quantile normalization, and Beta MIxture Quantile dilation (BMIQ) procedure to 572 remove type I/type II probes bias, as described elsewhere (Fiorito et al, 2017). DNAm levels 573…”
Section: Dna Methylation Analysis 554mentioning
confidence: 99%
“…Furthermore, it has been shown that 'age acceleration', defined as having a greater DNA 53 methylation age than chronological age, is associated with multiple risk factors of mortality 54 such as low social class, smoking, and alcohol use (Fiorito et al, 2017) 2016) combined a small set of markers to provide an overall assessment of biological 62…”
Section: Introduction 29mentioning
confidence: 99%
See 1 more Smart Citation
“…The variance of epigenetic age acceleration has also been suggested to be influenced by environmental factors [22]. Lifestyle factors, such as smoking, alcohol drinking, obesity, exercise and diet [23,19,[24][25][26], and hormone-related breast cancer risk factors, such as age at menarche and age at menopause [27,28], have been found to be associated with epigenetic age acceleration.…”
Section: Introductionmentioning
confidence: 99%